Nabokov's favorite word is mauve : what the numbers reveal about the classics, bestsellers, and our own writing - Blatt, Ben (Simon & Schuster, 2017)
In Nabokov's Favorite Word Is Mauve, statistician and journalist Ben Blatt brings big data to the literary canon, exploring the wealth of fun findings that remain hidden in the works of the world's greatest writers. He assembles a database of thousands of books and hundreds of millions of words, and starts asking the questions that have intrigued curious word nerds and book lovers for generations: What are our favorite authors' favorite words? Do men and women write differently? Are bestsellers getting dumber over time? Which bestselling writer uses the most clichés? What makes a great opening sentence? How can we judge a book by its cover? And which writerly advice is worth following or ignoring? Blatt draws upon existing analysis techniques and invents some of his own. All of his investigations and experiments are original, conducted himself, and no math knowledge is needed to understand the results. Blatt breaks his findings down into lucid, humorous language and clear and compelling visuals. This eye-opening book will provide you with a new appreciation for your favorite authors and a fresh perspective on your own writing, illuminating both the patterns that hold great prose together and the brilliant flourishes that make it unforgettable.